Government and Cities: Contests and the Decentralization of Decision Making - Gil S. Epstein; Ira N. Gang (Institute for the Study of Labor (IZA), 2002)
Governments do not have perfect information regarding the priorities and the needs of different groups in the economy. This lack of knowledge opens the door for different groups to lobby the government in order to receive the government?s support. We set up a model of hierarchical contests and compare the implications of a centralized allocation process with a decentralized allocation process. We show the potential existence of a poverty trap as a result of fiscal federalism.
Keywords: D72; H77; H73; 330; fiscal federalism; economic models of political processes; contests; rentseeking; intergovernmental relations; Finanzföderalismus; Rent Seeking; Finanzausgleich; Vereinigte Staaten